Respiratory infections: a global burden - José, Ricardo J. (Annals of Research Hospitals, 2018)
Respiratory infections are accountable for significant morbidity, and mortality world-wide. Amongst all diseases, lower respiratory tract infections have the greatest burden on human health, with a two and six-fold greater disability-adjusted life years compared to ischaemic heart disease and diabetes mellitus, respectively (1).